Persona, Trauma and Transformation in The Silent Patient and Black Swan: A Psychoanalytical Critique - Zill E Maryam; Rahat Bashir (`, 2025)
The self is shaped not only by what is consciously expressed, but also by what remains silently carried within. This study explores the role of unconscious emotional memory and trauma in early development years on the psychological dynamics of the main characters, which eventually results in identity fragmentation and mental disintegration. This qualitative and interpretive research examines how The Silent Patient and Black Swan illustrate the development and transformation of persona, drawing parallels between the protagonists’ psychological journeys and the theories of Bollas and Winnicott. It focuses how both works demonstrate the consequences of suppressing the authentic self in favor of societal expectations, leading to psychological distress and eventual breakdown. The investigation employs comparative textual analysis to address the similarities between the theoretical constructs of Bollas and Winnicott, especially the role played by early object relations in the development of personality and the process by which repressed emotional links are expressed in self-destructive actions. It is concluded that the two stories show the devastating effects of prioritizing societal norms over true self-expression, which leads to the creation of stiff defense mechanisms that make it impossible to experience a real relationship with emotions and become a person. Moreover the analysis reveals the paramount significance of bringing in seamless emotional experience with conscious identity, and points to the clinical relevance of identifying and expressing the unthought known in clinical work. Key Words: Persona, Trauma, Transformation, Unconscious, False self